Political Dynamics of Women's Village Head Leadership (Journal of Namibian Studies : History Politics Culture, 2023)
This study examines the Political Dynamics of Women's Reje Village (Village Head) Leadership in Bener Mulie Village, Wih Pesam District, Bener Meriah Regency. This study aims to discover how the political dynamics carried out by Reje Bener Mulie, Wih Pesam sub-district, Bener Meriah Regency, and why the crisis of Trust in the Bener Mulie people has disappeared. The approach taken in this study is a qualitative method using Leadership Theory and Political Process Theory. Based on this research, the political dynamics carried out by Reje Kampung Bener Mulie needed to meet the expectations of the community both in the field of work and outside of work. Reje has negative attitudes towards the Bener Mulie village community. So that this causes the community to have their own opinions related to Reje's performance during his term of office. The cause of the crisis of public Trust in Reje consisted of changes in Reje's attitude before and after serving as Village Head (Village Head) of the community. Reje did not keep promises made during the Reje Kampung election period; Reje was not responsible for carrying out his duties as Reje Kampung, especially in development and food security in 2021.